Design, synthesis and photochemical properties of the first examples of iminosugar clusters based on fluorescent cores - Lepage, Mathieu L.; Mirloup, Antoine; Ripoll, Manon; Stauffert, Fabien; Bodlenner, Anne; Ziessel, Raymond; Compain, Philippe (Beilstein Journal of Organic Chemistry, 2015)
The synthesis and photophysical properties of the first examples of iminosugar clusters based on a BODIPY or a pyrene core are reported. The tri- and tetravalent systems designed as molecular probes and synthesized by way of Cu(I)-catalysed azide–alkyne cycloadditions are fluorescent analogues of potent pharmacological chaperones/correctors recently reported in the field of Gaucher disease and cystic fibrosis, two rare genetic diseases caused by protein misfolding.
Keywords: BODIPY; fluorescent probes; iminosugars; 4-methylumbelliferone; multivalency; pyrene